Ionization effects on spectral signatures of quantum-path interference in high-harmonic generation - Holler,MH; Zair,AZ; Schapper,FS; Auguste,TA; Cormier,EC; Wyatt,ASW; Monmayrant,AM; Walmsley,IAW; Gallmann,LG; Salieres,P; Keller,UK (Optics Express, 2009)
The interference between the emission originating from the short and long electron quantum paths is intrinsic to the high harmonic generation process. We investigate the universal properties of these quantum-path interferences in various generation media and discuss how ionization effects influence the observed interference structures. Our comparison of quantum-path interferences observed in xenon, argon, and neon demonstrates that our experimental tools are generally applicable and should also allow investigating more complex systems such as molecules or clusters.